Do Aquatic Macrophytes Limit the Invasion Potential of Exotic Species in Pantanal Grasslands? - Bao, Francielli [UNESP]; Elsey-Quirk, Tracy; de Assis, Marco Antonio [UNESP]; de Souza, Evaldo Benedito; Pott, Arnildo (Springer Nature, 2019)
Natural disturbances have the potential to limit exotic species invasions. The exotic grass, Urochloa humidicola, has high propagation potential following seasonal flooding, but, flooding tends to reduce the cover. Neither the potential for U. humidicola form a seed bank for recruitment following seasonal flooding, nor the mechanism responsible for reducing adult plant cover during floods is currently known. The soil seed bank of a U. humidicola was sampled for 2 years. To examine the potential role of competition with aquatic macrophytes in reducing its cover during floods, cuttings of U. humidicola were flooded in tanks in presence and absence of aquatic macrophytes for 3 months. Seedling density of U. humidicola was higher post-flood (245 seedlings/m −2 ) than the post-dry (130 seedlings/m −2 ). Germination occurred throughout the year, with highest seedling densities at the five to 7 months following soil collection. Competition with aquatic plants significantly increased mortality (c. 70%) of inundated U. humidicola. Our findings suggest that the survival potential of U. humidicola under flood is high, but is limited by shading of aquatic macrophytes. Nonetheless, its seed bank germinates throughout the year, though delayed by flooding. Control of invasive species in grasslands of the Pantanal depend on natural hydrological and biological drives.
Keywords: Aquatic plants; Flood tolerance; Seed bank; Wetland